The B Corp certification model applied to Iscte Executive Education - Macedo, Maria José dos Reis de (2021)
In this master thesis of company-project type, the B Corp certification model was applied to the ISCTE Executive Education organization, to provide a diagnosis on its level of contribution to the sustainable development of the planet and to identify the improvement actions that can be implemented. The score obtained is 65.6, below the minimum eligible for certification. Customers is the impact area where ISCTE Executive Education’s sustainable performance is better. Workers is the second contributor to the final score but presents low score in most of the topics. The chapters that poorly scored are Governance and Environment, followed by Community. A comparison to other organizations that have applied the same model was performed. The total scores were also compared to certified organizations of the same industry and a similar trend was identified. Comparatively, Workers is the impact area where ISCTE Executive Education presents the worst performance followed by Environment. The impact areas where ISCTE Executive Education is performing better than others are Customers, followed by Governance and Community. The recommended actions to improve this score were prioritized and organized in clusters. A TO BE scenario was presented and quantified.